The Modelling of Strengthening Indicators Development in Regional Innovation System and Its Effect on the Gross Domestic Product - Sitompul, Rislima F.; Sumule, Ophirtus (Research and Development Agency Ministry of Home Affairs, 2016)
This study aims to revise the indicators of measuring Regional Innovation System (SIDa) component in order to simplify the measurement such that it can directly influence the improvement of success indicators in a region or district. Measuring the components of SIDa for all regions are necessary as the baseline of policy parameters for the Government in developing SIDa so that the implementation the policy on innovation systems become more effective. In this study, the modeling is focused on refining the existing parameters that have been previously developed for strengthening policy implementation of SIDa applied in each region. Modeling and development of these indicators are required in order to result as a reference for solving problems in the implementation of SIDa and can be used as reference material to establish an appropriate and effective patterns of regional development approach. The analysis tool used is multiple regression analysis using an Ordinary least square technique. Results of regression modeling produced a valid model with all independent variables significant and positive impact on the SIDa. Regression analysis shows that strengthening SIDa of all provinces in Indonesia provide significant and positive impact in increasing the Gross Domestic Products (GDP). Likewise, the success indicators show the positive effect, which means that implementation of SIDa has proven to increase the benchmark indicators of the region.